ANALISIS SAMPUL BUKU TEMA PERKEMBANGAN TEKNOLOGI: ANALISIS SAMPUL BUKU TEMA PERKEMBANGAN TEKNOLOGI - yurike bala; Rahmat Olii (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
Textbooks are textbooks in certain fields, which are learning tools that will be developed according to the curriculum in relevant learning policies. One of the textbooks in a certain field is an integrated thematic book with the title of the 7th theme book